Early Growth Response 1 (Egr1) Is a Transcriptional Activator of NOX4 in Oxidative Stress of Diabetic Kidney Disease - Fang Hu; Meng Xue; Yang Li; Yi-Jie Jia; Zong-Ji Zheng; Yan-Lin Yang; Mei-Ping Guan; Liao Sun; Yao-Ming Xue (Journal of Diabetes Research)
Background. NADPH oxidase 4 (NOX4) plays a major role in renal oxidative stress of diabetic kidney disease (DKD). NOX4 was significantly increased in Egr1-expressing fibroblasts, but the relationship between Egr1 and NOX4 in DKD is unclear. Methods. For the evaluation of the potential relationship between Egr1 and NOX4, both were detected in HFD/STZ-induced mice and HK-2 cells treated with TGF-β1. Then, changes in NOX4 expression were detected in HK-2 cells and mice with overexpression and knockdown of Egr1. The direct relationship between Egr1 and NOX4 was explored via chromatin immunoprecipitation (ChIP). Results. We found increased levels of Egr1, NOX4, and α-SMA in the kidney cortices of diabetic mice and in TGF-β1-treated HK-2 cells. Overexpression or silencing of Egr1 in HK-2 cells could upregulate or downregulate NOX4 and α-SMA. ChIP assays revealed that TGF-β1 induced Egr1 to bind to the NOX4 promoter. Finally, Egr1 overexpression or knockdown in diabetic mice could upregulate or downregulate the expression of NOX4 and ROS, and α-SMA was also changed. Conclusion. Our study provides strong evidence that Egr1 is a transcriptional activator of NOX4 in oxidative stress of DKD. Egr1 contributes to DKD by enhancing EMT, in part by targeting NOX4.